If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(6m + 7) = -2 + -7m Reorder the terms: 5(7 + 6m) = -2 + -7m (7 * 5 + 6m * 5) = -2 + -7m (35 + 30m) = -2 + -7m Solving 35 + 30m = -2 + -7m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '7m' to each side of the equation. 35 + 30m + 7m = -2 + -7m + 7m Combine like terms: 30m + 7m = 37m 35 + 37m = -2 + -7m + 7m Combine like terms: -7m + 7m = 0 35 + 37m = -2 + 0 35 + 37m = -2 Add '-35' to each side of the equation. 35 + -35 + 37m = -2 + -35 Combine like terms: 35 + -35 = 0 0 + 37m = -2 + -35 37m = -2 + -35 Combine like terms: -2 + -35 = -37 37m = -37 Divide each side by '37'. m = -1 Simplifying m = -1
| s-9/10=21/10 | | 2(3w-12+w)=640 | | -9p=-72 | | 1.96x^5-4x^2-16x-16=0 | | 7-7(1-7x)=8x | | p(x)=-2x+100x-25 | | s-7/10=13/10 | | 12y=13.2 | | 5x+1+3=8(3x+2)+7(2-3x) | | 7(2y+1)=3(7+5y) | | X+x+.11+x+.11+.38=10.32 | | (2x+10)=(2x-15) | | 2(w+20+w)=380 | | -(1+6n)=-152 | | 121=0 | | 18-[2+3(8-5)]= | | 8(2+2x)-6=90 | | (x-2)2+(y+6)2=25 | | 2(x-3)+9=2x+2 | | X+5x+13=140 | | 1/2x=121 | | 19-5x/2=33 | | Y=6(6)-2 | | -x^2+5x+3=0 | | Y=6(4)-2 | | -4z+6x-2y+2z-3y= | | 3x/4x-2-2x/6x-3=5/2x-1 | | 14x+4+18x-4+14x-8=360 | | (6x-9)(3x+4)=0 | | 5/6=x/32 | | x/8=x/9-7 | | 3n-2÷5=7/10 |